FENOMENA PENGGUNAAN BAHASA GAUL DI KALANGAN SISWA SD KELAS IV TERHADAP PENGGUNAAN BAHASA INDONESIA - Abilson Ginting; Araida Purba; Muthia Resty; Elly Prihasti Wuriyani; Khairil Anshari (Kampus Akademik Publiser, 2025)
The rapid development of technology and media has had a significant impact on various aspects of society, including the use of good and correct language. Recently, a new trend has emerged among elementary school students, known as slang. Slang Refers to the use of informal language that often contains trendy terms in everyday conversation. Examples of common slang words used include